Clinical Knowledge of Final-Year Dental Students Regarding the Dental Management of Pregnant Women: A Cross-Sectional Study in Public Universities of São Paulo, Brazil - Ana Laura Martins Ferreira; Luis Eduardo Genaro; Fernanda Lopez Rosell (Odovtos - International Journal of Dental Sciences, 2026)
This study aimed to evaluate the clinical knowledge of final-year dental students from public universities in the state of São Paulo regarding the management of pregnant women in dental care. An observational, cross-sectional study was conducted with 63 final-year dental students from six public universities. A structured and self-administered questionnaire assessed sociodemographic variables, aspects of undergraduate training, and specific domains of clinical knowledge related to pregnancy management in dentistry (timing of procedures, anesthetic use, radiographic safety, medication prescription, and preventive care). Data were analyzed in JAMOVI using Fisher’s exact test (α=0.05). Overall, students demonstrated intermediate to satisfactory levels of clinical knowledge. Most participants correctly recognized the importance of oral health during pregnancy (60.3%), identified the second trimester as the safest period for most procedures (47.6%), and selected lidocaine as the anesthetic of choice (82.5%). Furthermore, 60.3% indicated awareness of appropriate radiographic protection protocols, and 79.3% reported that fluoride use is safe during pregnancy. A statistically significant association (p